A novel approach for HLA-A typing in formalin-fixed paraffin-embedded-derived DNA (2014)
The aim of this study was to establish a novel approach for human leukocyte antigen (HLA)-typing from formalin-fixed paraffin-embedded-derived DNA. HLAs can be a prognostic factor in cancer and have an extensive polymorphism. This polymorphism is predominantly restricted to exons, which encode the peptide-binding domain of the protein. Formalin-fixed paraffin-embedded material is routinely collected in the clinic and therefore a great source of DNA for genetic analyses. However, its low quality due to fragmentation and nucleotide changes has often created obstacles in designing genetic assays. In this study, we amplified the most polymorphic exons of the HLA-A gene, exons 2, 3, and 4, in 16 formalin-fixed paraffin-embedded samples >10 years old. These tissue samples belonged to patients already HLA-typed by peripheral blood samples at the routine laboratory. Acquired amplification products were used for sequencing, which provided enough information to establish an HLA allele. The same method was applied to DNA extracted from peripheral blood from a healthy volunteer with known HLA type. Of the samples, 14/16 (88%) were successfully typed, in one sample only one of the alleles could be determined, and in one sample no allele could be determined. The amplification of the most polymorphic exons of HLA-A was a successful alternative when DNA quality prevented positive results with previously described methods. The method is usable when an HLA type is needed but the patients are deceased and/or no whole blood samples can be collected. It has thus potential to be used in several fields such as the clinic, research, and forensic science. © 2014 USCAP, Inc All rights reserved.